Pengaruh Promosi Kesehatan Dengan Media Film Terhadap Pengetahuan Pencegahan Hipertensi Pada Lansia Di UPTD Puskesmas Tanjung Unggat - Rani Fitriana Rahman; Siska Natalia; Fitriany Suangga (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension is a disease that often attacks the elderly. Health promotion that has been carried out so far has only been through outreach media, and creative media is needed to be able to convey the message of preventing worsening of hypertension sufferers. The aim of the research was to determine the influence of health promotion using film media on knowledge of hypertension prevention in the elderly at the Tanjung Unggat Community Health Center UPTD. This research used a pre-experimental design with a one-group pre-test-post-test design, with a population of 150 people and a sample of 33 respondents selected using purposive sampling. This research data collection tool uses a knowledge questionnaire. The results of this research are that the majority of respondents' knowledge before being given health promotion, 28 respondents (84.8%) were in the poor category. Meanwhile, after being given health promotion, 26 respondents (78.8%) were in the high category. The bivariate test results in this study used the Wilcoxon test with a p value of 0.000 (p value < 0.05). In conclusion, it is stated that health promotion using film media on knowledge of hypertension prevention in the elderly has a significant influence. Suggestions for future researchers to use other creative methods so that optimal health can be achieved.